Preliminary study on the preparation of latex foam rubber from graft copolymer of deproteinised natural rubber and methyl methacrylate - Nakason C; Kaesaman A; Ketsarin K; Yimwan N (Journal of Rubber Research, 2001)
Deproteinised natural rubber (DPNR) latex was prepareed by incubation of fresh field natural rubber latex with a proteolytic enzyme in the presence of an emulsifier. The nitrogen content was decreased from 0.9;(in the fresh field natural rubber letex) to 0.07;(in the DPNR). A graft copolymer of the deproteinised natural rubber latex and poly(methyl methacrylate) as a redox initiator. The presence of grafted PMMA in the natural rubber molecules was confirmed using FTIR. Intense absorption peaks at 1732 cm-1 (-C=0 stretch) and 1140 cm-1 (-C-0 stretch) were observed. It was also found that hardness, compression set and density of the latex foam rubber increased with the increase in the level of graft copolymer in compounding formulation. Furthermmore, at the same blend ratio, the properties increased with the increase in the level of methyl methacrylate used in the grafting reaction.
Keywords: Deproteinised natural rubber; FTIR; Graft copolymer; Latex foam rubber; Methylacrylate